Enhanced structural damage behavior of liquid-filled tank by reactive material projectile impact - Jianwen Xie; Yuanfeng Zheng; Zhenyang Liu; Chengzhe Liu; Aoxin Liu; Pengwan Chen; Haifu Wang (Defence Technology, 2024)
A series of ballistic experiments were performed to investigate the damage behavior of high velocity reactive material projectiles (RMPs) impacting liquid-filled tanks, and the corresponding hydrodynamic ram (HRAM) was studied in detail. PTFE/Al/W RMPs with steel-like and aluminum-like densities were prepared by a pressing/sintering process. The projectiles impacted a liquid-filled steel tank with front aluminum panel at approximately 1250 m/s. The corresponding cavity evolution characteristics and HRAM pressure were recorded by high-speed camera and pressure acquisition system, and further compared to those of steel and aluminum projectiles. Significantly different from the conical cavity formed by the inert metal projectile, the cavity formed by the RMP appeared as an ellipsoid with a conical front. The RMPs were demonstrated to enhance the radial growth velocity of cavity, the global HRAM pressure amplitude and the front panel damage, indicating the enhanced HRAM and structural damage behavior. Furthermore, combining the impact-induced fragmentation and deflagration characteristics, the cavity evolution of RMPs under the combined effect of kinetic energy impact and chemical energy release was analyzed. The mechanism of enhanced HRAM pressure induced by the RMPs was further revealed based on the theoretical model of the initial impact wave and the impulse analysis. Finally, the linear correlation between the deformation-thickness ratio and the non-dimensional impulse for the front panel was obtained and analyzed. It was determined that the enhanced near-field impulse induced by the RMPs was the dominant reason for the enhanced structural damage behavior.